2012
DOI: 10.4028/www.scientific.net/kem.510-511.284
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Impedance Spectroscopy Study of Al-Zn and Al-Zn-Sn Alloys in Tropical Seawater

Abstract: In this paper, a study on the electrochemical behaviour and electrical properties of Al-Zn and Al-Zn-Sn alloys in tropical seawater using open circuit potential (OCP) measurement and electrochemical impedance spectroscopy (EIS) are reported. The results from both the OCP and EIS tests show that surface activation was observed in the Al-Zn alloy with the addition of 1.34 wt.% Sn which can be manifested by the shift of OCP values towards more electronegative direction. The EIS spectra of Al-Zn alloy exhibits a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The corrosion characteristics of the Al and Al-5 Mg coating is assessed by OCP measurement with immersion duration, and the results are shown in Figure 6. During initial periods of immersion, both coatings exhibited electropositive OCP attributed to the formation of native oxide [45][46][47] and yet not observed in XRD on the Al coating, while Al-5 Mg coating exhibited uniform morphology and a high contact angle that does not allow the solution to ingress into the coating. This result is corroborated by other authors [48,49].…”
Section: Open Circuit Potential (Ocp) Measurementsmentioning
confidence: 96%
“…The corrosion characteristics of the Al and Al-5 Mg coating is assessed by OCP measurement with immersion duration, and the results are shown in Figure 6. During initial periods of immersion, both coatings exhibited electropositive OCP attributed to the formation of native oxide [45][46][47] and yet not observed in XRD on the Al coating, while Al-5 Mg coating exhibited uniform morphology and a high contact angle that does not allow the solution to ingress into the coating. This result is corroborated by other authors [48,49].…”
Section: Open Circuit Potential (Ocp) Measurementsmentioning
confidence: 96%
“…35 Sn is selected as an alternative activator for the Al sacrificial anodes 36 which depends on the added amount 3 and on the type of heat treatment that the alloy undergoes. [37][38][39][40][41][42] Khireche et al 3 have shown that 0.1% to 0.4% tin addition acts as Al-Zn alloy deactivator. This is due to the decrease of grain size, an increase of their density, and shift of the Al alloys potential to more negative values.…”
mentioning
confidence: 99%
“…Although indium is a suitable candidate for activation, it is also an expensive material. 36,41,42 An additional motivation for this choice concerns the corrosion products of Al-Zn-Mg alloys which are similar to those already present in seawater, thus preventing the pollution of marine life 62 and considered as eco-friendly sacrificial anodes. 63 The selected systems, Al-5%Zn-0.5%Sn and Al-5%Zn-0.5%Sn-2.6% Mg alloys are based on the precipitation and distribution of fine intermetallic phases in the α-Al matrix generated by heat treatment.…”
mentioning
confidence: 99%